Peningkatan Kualitas Semen “X” dengan Metode Six Sigma di Packing Plant PT. XYZ - Vera Devani; Nurul Amalia Nurul Amalia (JURNAL TEKNIK INDUSTRI, 2018)
PT. XYZ is a company engaged in cement packing plant. When the packing process takes place, there are often work process errors that cause product defects. Six sigma is a method used to improve product quality to produce defect-free products (zero defects) using the DMAIC approach (Define, Measure, Analyze, Improve and Control). The purpose of this research is to improve the quality of X cement products and to achieve zero defects during the packing process. Based on the research, it can be concluded that the types of defects found in the packing process are burst bag, stuck bag, out of tolerance bag weight, damaged bag, with the largest type of defect, namely 72.9% bag burst for 50 kg and 68 bag types, 8% for 40 kg bag types which will be prioritized for repairs. Sigma values for the type of bag 50 kg and 40 kg are in the range of values from 3.79 to 4.13σ. So that improvements still need to be made to achieve the 6σ value and to produce a zero defect product.